Physicochemical and microbial quality of cow and buffalo raw milk collected from different organized dairy farms of Varanasi, India - Lal, Dwarki; Rai, Dinesh Chandra; ., Arvind; Bhateshwar, Vinod; Muwal, Hitesh (Indian Journal of Dairy Science, 2021)
The current study was carried out to estimate the physicochemical properties, microbial quality, and adulteration pattern of cow and buffalo raw milk collected from different organized dairy farms in Varanasi, India. Raw milk samples were analyzed and found that the cow’s raw milk constituents i.e. the per cent of lactose (4.31) was significantly (P